Industrial training report: Universiti Sultan Azlan Shah - Jamal, Nurulhuda (Universiti Teknologi MARA, Perlis, 2024)
This report highlights my internship journey from 1st March until 14th August 2024 at Universiti Sultan Azlan Shah, located at Kuala Kangsar, Perak. For my internship role, I was assigned to the Human Resources and General Administration specifically in the Staffing and Service Unit under Mrs. Hasmida where my responsibilities varied within the administrative duties such as answering phone calls, assisting visitors at the counter, updating staff book services, scanning and printing, delivering documents, and other administrative-related tasks. My goal from this internship is to gain as much administrative knowledge and skills as possible in this department. This report will focus on analyzing the organization's SWOT analysis, SWOT Matrix, and PESTEL strategies to evaluate how it manages its operations based on these frameworks. Throughout of 24 weeks of my internship, I gained so much knowledge and skills regarding administrative job responsibilities such as managing staff book services, data entry, and customer service. It also enhances my multitasking skills and productivity where I can enhance my performance and display my abilities in completing the tasks given. Additionally, I had the opportunity to engage with various departments, which broadened my understanding of how different functions within the organization interconnect. This hands-on experience allowed me to refine my communication skills, as I often had to liaise between teams and ensure that information was accurately conveyed. One of the most rewarding aspects of the internship was the mentorship I received from seasoned professionals. Their guidance not only helped me navigate the complexities of the job but also inspired me to pursue further growth in this field. The feedback and constructive criticism I received were invaluable in shaping my professional demeanor and work ethic. As I move forward in my career, I am confident that the experiences and lessons learned during this internship will serve as a strong foundation. I am eager to apply my newfound skills and continue developing both personally and professionally, contributing positively to any future role I undertake.